2012
DOI: 10.1007/s10886-012-0076-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mating Success of Female Tortricid Moths Following Intense Pheromone Auto-Exposure Varies with Sophistication of Mating System

Abstract: Mating disruption is a valuable tool for the management of pest lepidopteran species in many agricultural crops. Many studies have addressed the effect of female pheromone on the ability of males to find calling females but, so far, fewer have addressed the effect of pheromone on the mating behavior of females. We hypothesized that mating of female moth species may be adversely affected following sex pheromone auto-exposure, due to abnormal behavioral activity and/or antennal sensitivity. Our results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
0
24
2
Order By: Relevance
“…These mechanisms do not work independently of each other, but rather in concert to interfere with sex pheromone communication of insect pests (Sanders, 1997). Recent evidence suggests that mating disruption may also be mediated by effects of pheromone treatment on female reproductive behaviors (Kuhns et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms do not work independently of each other, but rather in concert to interfere with sex pheromone communication of insect pests (Sanders, 1997). Recent evidence suggests that mating disruption may also be mediated by effects of pheromone treatment on female reproductive behaviors (Kuhns et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, research has not yet evaluated the effects on females of the frequency and level of exposure to pear ester alone and in combination with codlemone on behaviours that have been previously evaluated with codlemone alone, such as adult positioning in the canopy, calling duration and frequency and mating success (Weissling and Knight , ; Kuhns et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Their conclusion is contradicted by a series of reports on combo dispenser activity that have progressively demonstrated that the loading dose formulation of PVC dispensers can be substantially reduced and made more subtle for both codlemone and pear ester content while still achieving comparable disruption activity Stelinski et al 2007Stelinski et al , 2013Bohnenblust et al 2011;Knight et al 2012a, b). Unfortunately, research has not yet evaluated the effects on females of the frequency and level of exposure to pear ester alone and in combination with codlemone on behaviours that have been previously evaluated with codlemone alone, such as adult positioning in the canopy, calling duration and frequency and mating success Knight 1995, 1996;Kuhns et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mating disruption (MD) is a pest management technique where the ability of males and females to access each other is interfered with via competitive, false-trail following, induced allopatry, and induced arrestment (Miller & Gut, 2015;Miller, Gut, De Lame, & Stelinski, 2006b;Miller, Siegert, Amimo, & Walker, 2009), and/or noncompetitive, desensitization or habituation (Jones & Aihara-Sasaki, 2001;Kaissling, 1986;Stelinski, Gut, & Miller, 2003a;Stelinski, Miller, & Gut, 2003b), camouflage or when the signal is impaired between males and females (Kuhns, Pelz-Stelinski, & Stelinski, 2012;Schröder & Hilker, 2008) mechanisms. In recent years, commercial treatments using sex pheromone-based MD have increased 75%, covering 750,000 hectares across the globe and targeting more than 20 species (Carde & Minks, 1995;Miller & Gut, 2015;Wenninger & Averill, 2006).…”
Section: Introductionmentioning
confidence: 99%